P.061 The value of AVXS-101 gene-replacement therapy for Spinal Muscular Atrophy Type 1 (SMA1). (June 2019) - Dabbous, O; Sproule, DM; Feltner, DE; Droege, M; Khan, F; Arjunji, R
Abstract : Background: SMA1, a rapidly progressing disease, results in muscle weakness, respiratory failure, hospitalization, and early death. This study highlights the value of onasemnogene abeparvovec (AVXS-101) gene-replacement therapy for SMA1. Methods: Twelve SMA1 patients received a one-time intravenous proposed therapeutic dose of AVXS-101 (CL-101; NCT02122952). Event-free survival (no death/permanent ventilation), pulmonary/nutritional interventions, swallow function, hospitalization rates, CHOP-INTEND, motor milestones, and safety were assessed (2-year follow-up). Results: By study end, all 12 patients survived event-free; 7 did not require non-invasive ventilation; 11 had stable/improved swallowing function (6 exclusively fed by mouth); 11 spoke. On average, patients experienced 1.4 (SD=0.41, range=0–4.8) respiratory hospitalizations/year. The mean proportion of time hospitalized was 4.4% (range=0–18.3%); mean unadjusted rate of hospitalization/year was 2.1 (range=0–7.6), with a mean hospital stay of 6.7 (range=3–12.1) days. CHOP-INTEND increased by 9.8 (SD=3.9) and 15.4 (SD=6.4) points at 1- and 3-months post-treatment. At long-term follow-up, 11 patients sat unassisted, 4 stood with assistance, and 2 walked. Adverse events included elevated serum aminotransferase levels, which were attenuated by prednisolone. Conclusions: AVXS-101 in CL-101 resulted in dramatic survival and motor function improvements. The reduced healthcare utilization in treated infants could decrease cost and alleviate patient, caregiver, and societal burden.